Deep immune B and plasma cell repertoire in non-small cell lung cancer - Patel, Akshay J.; Khan, Naeem; Richter, Alex; Naidu, Babu; Drayson, Mark T.; Middleton, Gary W. (Frontiers in Immunology, 2023)
Introduction B cells, which have long been thought to be minor players in the development of anti-tumor responses, have been implicated as key players in lung cancer pathogenesis and response to checkpoint blockade in patients with lung cancer. Enrichment of late-stage plasma and memory cells in the tumor microenvironment has been shown in lung cancer, with the plasma cell repertoire existing on a functional spectrum with suppressive phenotypes correlating with outcome. B cell dynamics may be influenced by the inflammatory microenvironment observed in smokers and between LUAD and LUSC. Methods Here, we show through high-dimensional deep phenotyping using mass cytometry (CyTOF), next generation RNA sequencing and multispectral immunofluorescence imaging (VECTRA Polaris) that key differences exist in the B cell repertoire between tumor and circulation in paired specimens from lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC). Results In addition to the current literature, this study provides insight into the in-depth description of the B cell contexture in Non-Small Cell Lung Cancer (NSCLC) with reference to broad clinico-pathological parameters based on our analysis of 56 patients. Our findings reinforce the phenomenon of B-cell trafficking from distant circulatory compartments into the tumour microenvironment (TME). The circulatory repertoire shows a predilection toward plasma and memory phenotypes in LUAD however no major differences exist between LUAD and LUSC at the level of the TME. B cell repertoire, amongst other factors, may be influenced by the inflammatory burden in the TME and circulation, that is, smokers and non-smokers. We have further clearly demonstrated that the plasma cell repertoire exists on a functional spectrum in lung cancer, and that the suppressive regulatory arm of this axis may play a significant role in determining postoperative outcomes as well as following checkpoint blockade. This will require further long-term functional correlation. Conclusions B and Plasma cell repertoire is very diverse and heterogeneous across different tissue compartments in lung cancer. Smoking status associates with key differences in the immune milieu and the consequent inflammatory microenvironment is likely responsible for the functional and phenotypic spectrum we have seen in the plasma cell and B cell repertoire in this condition.